2022
DOI: 10.1101/2022.11.27.518083
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hypoxic tumors are sensitive to FLASH radiotherapy

Abstract: Tumor hypoxia is a major cause of resistance to cancer treatments and especially to radiotherapy. To address this specifically, we investigated whether ultra-high dose rate FLASH radiotherapy could overcome this resistance. Tumor cells from various origins were engrafted subcutaneously in mice to provide a reliable and rigorous way to modulate oxygen supply by vascular clamping or carbogen breathing. Tumors were irradiated using a single 20 Gy fraction at both conventional (CONV) and FLASH dose-rates using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 60 publications
0
1
0
Order By: Relevance
“…Studies using 10 Gy whole brain irradiation revealed a dose-rate threshold of 100 Gy/s to trigger the FLASH effect, preserving neurogenesis and neuronal morphology while minimizing neuroinflammation [55,74]. Carbogen breathing during UHDR irradiation reversed the neuroprotection, demonstrating the influence of oxygen levels [41,44]. Further validations at lower dose rates and with a single fraction of 30 Gy confirmed neuroprotection, reducing reactive astrogliosis, microglial, and C3 complement activation.…”
Section: Cell and Preclinical Models In Brain And Lungmentioning
confidence: 90%
See 1 more Smart Citation
“…Studies using 10 Gy whole brain irradiation revealed a dose-rate threshold of 100 Gy/s to trigger the FLASH effect, preserving neurogenesis and neuronal morphology while minimizing neuroinflammation [55,74]. Carbogen breathing during UHDR irradiation reversed the neuroprotection, demonstrating the influence of oxygen levels [41,44]. Further validations at lower dose rates and with a single fraction of 30 Gy confirmed neuroprotection, reducing reactive astrogliosis, microglial, and C3 complement activation.…”
Section: Cell and Preclinical Models In Brain And Lungmentioning
confidence: 90%
“…One hypothesis suggests that the distinct types of DNA damage induced by FLASH-RT and conventional dose-rate irradiation contribute to the disparate responses of healthy and tumor cells [14]. Another perspective posits that solid tumors, often characterized by hypoxia, are less shielded from the transient hypoxia caused by FLASH-RT compared to healthy tissues, resulting in varied effects [41]. Furthermore, differences in the ability of cancer cells and normal cells to scavenge hydrogen peroxide products may contribute to the observed variations [42].…”
Section: Oxygen Depletion Effectmentioning
confidence: 99%
“…To overcome such problem, one can exploit utilizing “radiation-activated prodrug,” experimental compounds that can be chemically converted into active cytotoxic moiety only upon irradiating tumors [ 60 ] with FLASH RT. Interestingly though, Leavitt et al [ 61 ] have recently found that hypoxic tumors, which are artificially induced by clamping the flank tumors in mice respond better to FLASH RT than CONV RT and that FLASH RT elicit unique signaling pathways including efficient cell cycle arrest, inhibition of translation and ribosomal biogenesis, and enhanced hypoxia-inducible factor-1 (HIF-1) signaling and glycolytic metabolism. It would be exciting whether this observation can also be made in more physiologically relevant hypoxic tumors in vivo .…”
Section: Future Issues To Be Addressed With Flash Rtmentioning
confidence: 99%